2018
DOI: 10.3390/ma11081305
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Degradation of Optical Silicone Exposed to Harsh Environments

Abstract: Degradation mechanisms of silicone plates under harsh environment conditions are studied in this investigation. Environmental degradation of silicone free form, used as secondary optics in Light Emitting Diode LED lighting lamps and luminaires or any other applications requiring high quality optics being used, has negative implications for the optical performance. Degradation of silicone plates in harsh environment conditions was studied in salt bath and swimming water environments, using different light radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This has to do with the fact that optical components in LED packages have a central role in the optical performance of LED devices by controlling the emission of light from the device. In fact, any depreciation in lumen output may involve a chromaticity shift as well [161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176]. As already mentioned, an LED lamp is a complicated system, containing secondary lenses, reflective layers, and diffusers, all intended to achieve a desired light emission pattern.…”
Section: Degradation Of Optical Materialsmentioning
confidence: 99%
“…This has to do with the fact that optical components in LED packages have a central role in the optical performance of LED devices by controlling the emission of light from the device. In fact, any depreciation in lumen output may involve a chromaticity shift as well [161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176]. As already mentioned, an LED lamp is a complicated system, containing secondary lenses, reflective layers, and diffusers, all intended to achieve a desired light emission pattern.…”
Section: Degradation Of Optical Materialsmentioning
confidence: 99%
“…Silicones are known for many unusual properties, compared to organic polymers, including resistance to oxidation . As a result, they are preferentially used in oxidative environments, including sealing rings for UV lamps, thermally stable elements in light-emitting diodes (LEDs), etc . Silicone foams are attractive alternatives to less expensive organic foams because of their resistance to combustion, an extreme form of oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, silicones have been commonly adopted for encapsulation because of advantages, including high transmittance, thermal resistance, low moisture absorption, and low modulus. [5][6][7][8][9][10][11][12][13][14][15][16] However, silicones suffer from delamination and cracking after long-term operation (or in harsh conditions 17 ), leading to the degradation of the UV-LED packages. It was reported that modification of the composition of silicones could effectively improve their performance and characteristics.…”
mentioning
confidence: 99%